Perancangan Awal Model Interaksi Anak Dalam Teknologi Pembelajaran Virtual Reality Berbasis CCI - Tiara Wulan Sari Tiara Wulan Sari; Ria Andryani (PPPM Institut Teknologi Pagar Alam, 2026)
This study aims to design an initial model of child interaction in Virtual Reality (VR)-based learning using the Child–Computer Interaction (CCI) approach. The research is motivated by the growing use of VR technology in education, which has strong potential to enhance children’s engagement and learning motivation, yet often lacks interaction designs that align with children’s developmental characteristics. This study employs a Design and Development Research (D&D) method, focusing on the systematic design of educational systems. The research stages include analyzing the needs and characteristics of children aged 7–10 years, designing a conceptual interaction model, developing interaction flows, learning scenarios, and interface designs based on CCI principles. The results indicate that the proposed interaction model accommodates children’s cognitive and motor characteristics through simple interaction flows, engaging visual elements, and intuitive navigation that supports learning through a learning-by-playing approach. This initial interaction model is expected to serve as a guideline for developing child-friendly and effective VR-based learning systems.